Oral HIV pre-exposure prophylaxis use among pregnant and postpartum women: results from real-world implementation in Lesotho - Masenyetse, Lieketseng J.; Greenberg, Lauren; Samonyane, Felleng; Sekepe, Bokang; Mokone, Majoalane; Mokone, Mafusi J.; Tukei, Vincent J.; Beres, Laura K. (Frontiers in Reproductive Health, 2023)
Introduction: Lesotho has reached epidemic control, PrEP is an important component of maintaining that and of getting to the goal of eliminating mother-to-child transmission.We conducted a retrospective review of existing, routine PrEP health records in 26 health facilities in Lesotho. PrEP visit data were collected for pregnant and breastfeeding postpartum women screened for PrEP and/or enrolled in PrEP programs from January 1, 2019 through June 30, 2021 with follow-up data collected up to the date of data abstraction per site between October 2021 and May 2022. Poisson regression with robust variance was used to evaluate association between patient characteristics and continuation on PrEP.Results: Indications for starting PrEP were significantly associated with continuation in PrEP use. Women starting PrEP due to having a partner known to be living with HIV were the most likely to return for any follow up. In all age groups, the most common reason for starting PrEP was being in a serodiscordant relationship, though the proportion varies by age.As Lesotho is now in the process of optimizing PrEP use among pregnant and postpartum breastfeeding women, it is critical to revise data sources to capture information that will This is a provisional file, not the final typeset article link PrEP records and ANC/PNC records and document pregnancy/postpartumbreastfeeding status in order to better understand PrEP use and gaps in this population.